Tourism : principles, practices, philosophies - Goeldner, Charles R (John Wiley, 2015)
This is a revision of the most comprehensive and widely used introductory text for tourism and hospitality students worldwide. It covers theories, philosophies, and practices of tourism while introducing students to the development, structure, and impact of tourism on destinations and travelers alike. This edition features new professional profiles that give insights into tourism careers; more end-of-chapter review tools; a revised four-color insert; and more! The most comprehensive text available, Tourism, 11th Edition offers an undergraduate- or graduate-level introduction to this important industry.